KEPUASAN NASABAH MENABUNG DI BMT NU KANGEAN BERDASARKAN PROMOSI DAN PELAYANAN ISLAMI - Nanda Hidayan Sono; Luluk Awwaliyah (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to measure, analyze and determine how much influence Islamic promotion and services have on customer satisfaction in saving at BMT NU Kangean. This type of research is quantitative research. The population of customers who save at BMT NU Kangean is 1,200 customers. The sample determination formula in this study uses the Slovin formula, which produces a sample of 92 people using a significance level of 10% (0.1). Data collection was obtained by distributing questionnaires using a Likert scale to 92 respondents, and the data was processed using SPSS. The data analysis techniques used in this study are validity tests, reliability tests, classical assumption tests including normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, while hypothesis tests include partial tests, simultaneous tests, coefficients of determination and multiple linear regression analysis. So the results of the study indicate that the independent variables (Promotion and Islamic Services) are partially proven to have a significant effect on the dependent variable (Customer Satisfaction) with a significance value of 0.081 <0.1 or tcount 1.766> t table 1.66216 (Promotion) and with a significance value of 0.002 <0.1 or tcount 3.267> t table 1.66216 (Islamic Services). While simultaneously getting the results that promotion and Islamic services together have a significant effect on customer satisfaction in saving with a significance value of 0.000 <0.1 or Fcount> F table (9.860> 2.36) with a determination coefficient value of 0.163 or 16.3%.